Penambahan Naoh Pada Larutan Developer Terpakai Untuk Mendapatkan Developing Time Optimal - Laksita Nariswari Ardhani (Fakultas Kedokteran Gigi, 2026)
Film processing is a crucial stage in radiographic examination. Dental students at the Dental Hospital of Jember University (RSGMP) utilize manual chemical processing, where repetitive use leads to developer exhaustion and frequent, costly replacements. Furthermore, developer waste contains hazardous heavy metals like silver nitrate (AgNO3) and silver bromide (AgBr) that can pollute the environment. To reduce waste and hospital expenses, replenishment was performed by adding sodium hydroxide (NaOH). This study aimed to determine the ideal NaOH mass to restore used developer effectiveness. Four groups were tested using a post-test only control group design: a control (Og) and additions of 5g, 10g, and 15g of NaOH on Carestream GBX developer after 45 uses. Developing time was measured and analyzed using the Kruskal-Wallis test. The results indicated a significant decrease in developing time corresponding to the increase in NaOH addition. The developing times were 27.28 seconds for group one, 19.30 seconds for group two, 19.37 seconds for group three, and 11.85 seconds for group four. The addition of 15 grams of NaOH was found to be the most optimal without causing film damage. In conclusion, the addition of 15 grams of NaOH effectively restores developer effectiveness, reduces costs and waste, and supports sustainable practices at Dental Hospital of Jember University.
Finalisasi Juli 2026 hasyim
Keywords: Developer; NaOH